Preclinical biodistribution and safety evaluation of human iPSC-derived dopaminergic neural progenitor cells for Parkinson’s disease - Huang, Ying; Wen, Hairuo; Li, Lily; Li, Lulu; Li, Qianqian; Qin, Chao; Mao, Yiyang; Lin, Zhi; Jiang, Hua; Zhu, Frank; Li, Xiang; Geng, Xingchao (Frontiers in Cell and Developmental Biology, 2026)
IntroductionHuman pluripotent stem cells (PSCs) have the potential to revolutionize regenerative medicine, but their clinical safety has not been thoroughly investigated. We investigated the in vivo biodistribution, safety evaluation, and in situ tumorigenicity test of specific human iPSC-derived dopaminergic neural precursor cell (DAP) therapeutic products in a severe immunodeficient mouse model and established a method for detecting stereotactic drug delivery and distribution differentiation to support clinical trial dose justification and toxicity monitoring.MethodsFor the biodistribution study, DAPs were injected into the unilateral striatum of NSG mice, and the distribution and differentiation of the transplanted cells were determined via immunofluorescence staining and qPCR at 1-, 28-, 84-, and 168-days post-administration. The toxicity and tumorigenicity studies were carried out on NSG mice by administering saline, 1 × 105 DAP cells, 2 × 105 DAP cells, 0.01% iPSCs (2 × 105 cells) or 1% iPSCs (2 × 105 cells) per animal in accordance with the intended clinical dosage. After 28, 84, and 168 days, the mice were euthanized.ResultsBrain-only discovery of DAP markers (Ki67, FOXA2, OTX2, STEM101, and STEM121) and specific sequences of DAPs was confirmed. From 1- to 184-days, the copy number of Th first decreased but then increased; the expression of STEM121 decreased, and the neuronal cell marker proteins Th and STEM101 increased. Additionally, the differentiation target RNA Th was identified 28 days after administration, and both the differentiation ratio and degree increased. There was no evidence of toxicity from DAPs, and there were no tumors or abnormally proliferating cells detected.DiscussionThis study developed a novel method for determining biodistribution and differentiation in vivo, provided a strategy to evaluate the safety of iPSC derived DAPs, and showed their safety in mice. The data provides essential safety data for the clinical translation of DAPs and supports their phase I clinical trials in China and the United States.